Kirenol Inhibits the Function and Inflammation of Fibroblast-like Synoviocytes in Rheumatoid Arthritis in vitro and in vivo - Wu, Jing; Li, Qiang; Jin, Li; Qu, Yuan; Liang, Bi-Bo; Zhu, Xiao-Tong; Du, Hong-Yan; Jie, Li-Gang; Yu, Qing-Hong (Frontiers in Immunology, 2019)
Kirenol is a diterpenoid extracted from the Chinese herbal medicine Siegesbeckiae. Siegesbeckiae has been used to treat Rheumatoid arthritis (RA) in China for several centuries. RA is characterized by the proliferation of synoviocytes in inflamed synovia, as well as by their expression of inflammatory cytokines. In the present study, we found that Kirenol inhibited the migration, invasion, and proinflammatory of IL-6 secretion of RA-associated synovial fibroblasts (FLS) at a concentration of 100–200 μg/ml in vitro. Proinflammatory cytokines production and synovium hyperplasia and cartilage erosion were also inhibited in a collagen-induced arthritis (CIA) mouse model upon Kirenol treatment. Together, our results thus confirm that Kirenol has potent therapeutic efficacy in RA owing to its ability to suppress negative FLS activities.